FAKTOR-FAKTOR PENENTU TURNOVER INTENTION PEGAWAI BANK: PERAN WORK-LIFE BALANCE, STRES KERJA, KOMPENSASI, DAN KEPUASAN KERJA - Mochamad Syafruddin Aji; Ronny; Tanza Dona Pertiwi; Muhammad Cholil (Department of Management - Institut Shanti Bhuana, 2025)
The high employee turnover in Indonesia’s banking sector in recent years reflects intense pressure and demanding performance targets that may disrupt employees’ work-life balance and job satisfaction. This study aims to analyze the factors influencing bank employees’ turnover intention by examining the roles of work-life balance, job stress, and compensation, as well as testing job satisfaction as a mediating variable. A quantitative approach was employed through a survey of 104 bank employees in East Java, and the data were analyzed using SEM-PLS. The findings reveal that work-life balance and job stress have a significant effect on turnover intention, whereas compensation and job satisfaction show no significant effect. Moreover, job satisfaction does not mediate the effects of work-life balance, job stress, or compensation on turnover intention. These results indicate that in a target-driven banking industry, reducing turnover intention cannot be achieved merely by increasing compensation or relying on job satisfaction. The practical implications suggest that management should design more human-centered policies, such as setting realistic targets, monitoring workload, implementing flexible work arrangements, and establishing structured stress management programs. These efforts are essential to create a more supportive work environment that enables employees to maintain role balance without compromising performance, ultimately reducing their intention to leave the organization.